Challenges to technical and vocational education : keynote speech presented at the International Congress on Technical and Vocational Education (2nd, Seoul, South Korea, April 26-30, 1999) - Schmidt, Hermann [Verfasser] (My University, 1999)
„Advances in information technology are changing industrialized societies into knowledge societies. The end of the cold war has promoted development of a global economy. Growing ecological consciousness has necessitated that environmental knowledge become part of all education. As the need to remain competitive increases, a new balance in responsibility in the partnership between management and the work force has developed. Enabling people to cope successfully with anxiety and uncertainty has become one of the most important tasks of education. Learning to learn must become the overall objective of all education. All education, including vocational education and training (VET), must prepare young people for life by developing their intellect, aptitudes, and talents and by creating opportunities for them to reach their full potential. A new global movement toward new VET standards is evolving. The European Training Foundation, which was founded in 1994, has assisted Central and Eastern European countries in restructuring their VET systems by providing the following: information agencies (called observatories), an expert network to support development and implementation of VET standards, pilot projects in partner countries, tailored advice, and an information network. Much has already been done to improve VET globally; however, much more creativity and investment is needed.“ (excerpt; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 1.5 Internationale Organisationen & Institutionen; 370; Berufsbildung; Internationale Zusammenarbeit; Informationstechnik; Ökologie; Internationale Organisation